Nutritional Status among Adolescent Girls in Rural Areas of Tirupati - A Cross Sectional Study - Visweswara Rao Guthi; Neeraja Kolar; Nagaraj Kondagunta (Medsci Publications, 2022)
Background: Adolescent is the period of the life between the ages of 10-19 years. Adolescence is time to learn and adopt healthy habits to avoid many health and nutritional problems later in life. Objective of this study is to assess the nutritional status of adolescent girls by anthropometric measurements and to determine the association between different individual and family level factors with under nutrition. Methods: It is a community based cross-sectional study conducted among adolescent girls of age between 10-19 years in rural areas of Tirupati. The study sample was 188. BMI for age <-2SD is considered as thinness. A pre tested semi structured questionnaire was used to collect individual and family level factors and analysed using appropriate statistical tests with SPSS26th version. Results: Prevalence of thinness and overweight/obese among adolescent girls in this study was 17% and 17.6%. Thinness was significantly high among girls with family size is more than five(23.8% vs 8.4%), who attained menarche at >11 years (17.1% vs 0%) and who are not doing regular physical activity(22.3% vs 9.2%). Multivariate binary logistic regression showed socioeconomic status, family size and physical activity are significant predictors of thinness. Conclusions: It can be concluded from this study that thinness was significantly high among adolescent girls with family size >5, who attained menarche at >11 years and who does not have the habit of doing regular physical activity.